Electron‐Beam‐Evaporated Nickel Oxide Hole Transport Layers for Perovskite‐Based Photovoltaics. Issue 12 (4th February 2019) - Abzieher, Tobias; Moghadamzadeh, Somayeh; Schackmar, Fabian; Eggers, Helge; Sutterlüti, Florian; Farooq, Amjad; Kojda, Danny; Habicht, Klaus; Schmager, Raphael; Mertens, Adrian; Azmi, Raheleh; Klohr, Lukas; et al.
Abstract: High‐quality charge carrier transport materials are of key importance for stable and efficient perovskite‐based photovoltaics. This work reports on electron‐beam‐evaporated nickel oxide (NiO x ) layers, resulting in stable power conversion efficiencies (PCEs) of up to 18.5% when integrated into solar cells employing inkjet‐printed perovskite absorbers. By adding oxygen as a process gas and optimizing the layer thickness, transparent and efficient NiO x hole transport layers (HTLs) are fabricated, exhibiting an average absorptance of only 1%. The versatility of the material is demonstrated for different absorber compositions and deposition techniques. As another highlight of this work, all‐evaporated perovskite solar cells employing an inorganic NiO x HTL are presented, achieving stable PCEs of up to 15.4%. Along with good PCEs, devices with electron‐beam‐evaporated NiO x show improved stability under realistic operating conditions with negligible degradation after 40 h of maximum power point tracking at 75 °C. Additionally, a strong improvement in device stability under ultraviolet radiation is found if compared to conventional perovskite solar cell architectures employing other metal oxide charge transport layers (e.g., titanium dioxide). Finally, an all‐evaporated perovskite solar mini‐module with a NiO x HTL is presented, reaching a PCE of 12.4% on an active device area of 2.3 cm 2 . Abstract : A highly transparent nickel oxide hole transport layer prepared by oxygen‐assisted electron beam evaporation for perovskite‐based photovoltaics is reported. Using these layers in perovskite solar cells, efficient devices with stable power conversion efficiencies up to 18.5% for inkjet‐printed absorbers and 15.4% for co‐evaporated absorbers are demonstrated. In addition, good stability at elevated temperature and under ultraviolet radiation is shown.